1988
DOI: 10.1139/f88-219
|View full text |Cite
|
Sign up to set email alerts
|

A Space- and Time-Scale Characterization of Circulation and Mixing over Submarine Banks, with Application to the Northwestern Atlantic Continental Shelf

Abstract: The circulation and mixing over submarine banks is described in terms of integral space and time scales determined from Eulerian and Lagrangian currents. The time scales include the time for vertical diffusion across the pycnocline or water depth, the recirculation times of any residual gyre, and the residence time over the bank. These may be intercompared to obtain a description of a bank's physical regime and compared with the time scales associated with biological processes to identify possible physical–bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
1

Year Published

1990
1990
2002
2002

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 0 publications
3
30
1
Order By: Relevance
“…When the stratification index (S) was less than about 0.007, sea scallop larvae were distributed evenly over the whole water column, and can probably be con-sidered passive particles. As such, sea scallop larvae in the mixed areas of Georges Bank may be redistributed over the water column every 5 h (Loder et al 1988), and their horizontal movement should b e a function of the depth-averaged residual current. Above S values of 0.007, sea scallop larvae were aggregated below the surface, in several cases above or within the pycnocline.…”
Section: Discussionmentioning
confidence: 99%
“…When the stratification index (S) was less than about 0.007, sea scallop larvae were distributed evenly over the whole water column, and can probably be con-sidered passive particles. As such, sea scallop larvae in the mixed areas of Georges Bank may be redistributed over the water column every 5 h (Loder et al 1988), and their horizontal movement should b e a function of the depth-averaged residual current. Above S values of 0.007, sea scallop larvae were aggregated below the surface, in several cases above or within the pycnocline.…”
Section: Discussionmentioning
confidence: 99%
“…The circulation on Flemish Cap is characterized by a weak anticyclonic circulation (ca 3 to 5 cm S-' residual circulation) that can be disrupted by storms (Hill et al 1975, Hayes et al 1977, Ross 1980, Kudlo et al 1984. Loder et al (1988) reported a mean annual recirculation time of 67 to 78 d for near-surface waters along the 400 m isobath and a mean residence time of 32 to 40 d for near-surface waters within the 400 m isobath. They concluded there is sufficient residency time to be favourable to biological processes.…”
Section: Peak Spawningmentioning
confidence: 99%
“…The bank is typified by a large, well-known, mean residual clockwise gyre with a recirculation time (about 56 d) near its annual average residence time of 54 d (Flagg 1987, Lynch & Namie 1993. Variations in current suggest that in summer, when the gyre is at its strongest, residence time exceeds recirculation time, while in winter residence time tends to be about half and recirculation time about double the summer values (Loder et al 1988). It is thought that this gyre helps to retain larvae of fish on the bank (Bumpus 1976).…”
Section: Three Populations With Different Larval Habitatsmentioning
confidence: 99%